Analisis Tatakelola Pengelolaan Badan Layanan Umum Menggunakan Framework Control Objectives for Information dan SWOT - Rinaldi; Aryanaldi (SAFE-Network, 2024)
This research aims to conduct an analysis of the management of the UIN Imam Bonjol Padang Public Service Agency (BLU) using the COBOT 4.1 framework. Focus on using Plain and Organized Domains and SWOT analysis to determine opportunities, weaknesses, risks and opportunities as well as using the RACHI Chart table. The results of the analysis show that the leadership's concern for BLU management is very high, as evidenced by the formation of a work unit for BLU management and supported by a money budgeting policy for BLU management which is stated in the strategic planning document, although there are still weaknesses that need to be corrected.